A novel 3-D cuprous iodide polymer with a high Cu/I ratio. Issue 10 (16th February 2018) - Xiao, Hong; Zhou, Jian; Liu, Xing; Xiao, Hongping; Ferreira, Rute A. S.; Carlos, Luís D.; Fu, Lianshe
Abstract : The interconnection of rare 1-D cationic aggregates [CuI3I 2+ ] n and anionic bi-tetrazolate bridges leads to the formation of a novel 3-D cuprous iodide polymer with a Cu/I ratio as high as 3, which shows unusually thermochromic luminescent properties. Abstract : A novel 3-D cuprous iodide polymer [CuI3I(μ6 -L)] n with a Cu/I ratio as high as 3 (1, H2 L = 1, 3-bis(2 H -tetrazol-5-yl)benzene) has been hydrothermally synthesized. The 3-D framework of1 is constructed by the linkages of rare 1-D cationic aggregates [CuI3I 2+ ] n and anionic bi-tetrazolate bridges.1 shows unusually thermochromic luminescent and photocatalytic properties, and its density functional theory calculation has also been studied.